2022
DOI: 10.3389/fmed.2021.792487
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Ischemic Stroke and COVID-19 in China: A Population-Based Retrospective Study

Abstract: Background and PurposeTo investigate the effect of prior ischemic stroke on the outcomes of patients hospitalized with coronavirus disease 2019 (COVID-19), and to describe the incidence, clinical features, and risk factors of acute ischemic stroke (AIS) following COVID-19.MethodsIn this population-based retrospective study, we included all the hospitalized positive patients with COVID-19 at Wuhan City from December 29, 2019 to April 15, 2020. Clinical data were extracted from administrative datasets coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(38 reference statements)
0
8
0
Order By: Relevance
“…The fact that we had a higher percentage of COVID-19 (+) patients with a history of stroke who required ICU management or mechanical ventilation may be in part due to the low absolute number of patients with a history of stroke. However, prior large cohort studies have shown that COVID-19 (+) with a prior history of stroke tend to be older, have more comorbidities and develop worse clinical outcomes after COVID-19 [12,13].…”
Section: Discussionmentioning
confidence: 98%
“…The fact that we had a higher percentage of COVID-19 (+) patients with a history of stroke who required ICU management or mechanical ventilation may be in part due to the low absolute number of patients with a history of stroke. However, prior large cohort studies have shown that COVID-19 (+) with a prior history of stroke tend to be older, have more comorbidities and develop worse clinical outcomes after COVID-19 [12,13].…”
Section: Discussionmentioning
confidence: 98%
“…COVID-19 was first reported in Wuhan, China. There is no doubt that the city's experience has provided researchers with valuable information regarding the characterization and early treatment of COVID-19-related neurological disorders ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Schultz et al ( 57 ) found that a 0.55% incidence of CVT within 1 month since the first dose vaccination and that women are more likely to develop CVT after vaccination. Mechanistically, RAS system imbalance, endothelial damage, cytokine storm, hypercoagulable state, and impaired immune function are suspected to contribute to acute cerebrovascular events and deserve more research in future ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acute ischemic stroke concomitant with SARS-CoV-2 infection has been extensively described in the literature [ 28 , 52 •, 53 60 , 61 •, 62 ] ranging from 0.9 to 4.6% (Table 1 ). A representative CT scan image of patients with COVID-19 diagnosed with ischemic stroke in the distribution of the right posterior cerebral in the presence of vascular risk factors is shown in Fig.…”
Section: Clinical Cerebrovascular Manifestation Of Sars-cov-2mentioning
confidence: 99%
“…Intriguingly, some later studies indicated a different prevalence. In a retrospective study of 36,358 hospitalized patients from Wuhan, only 124 (0.34%) were diagnosed with AIS, which was correlated with severity of infection [ 53 ]. Furthermore, a multicentre study from New York identified 22 AIS incidents from 2513 COVID-19 cases (0.9%), with an OR of 0.35 (95% CI = 0.23–0.55) compared to a non-COVID-19 cohort [ 59 ].…”
Section: Clinical Cerebrovascular Manifestation Of Sars-cov-2mentioning
confidence: 99%